Analysis of Officer Soft Skills in Increasing Service Satisfaction to Customers Aceh Mental Hospital - Elly Sujiati; Nasrul Z; Said Usman; Irwan Saputra; Muhazar Muhazar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Mental hospitals in carrying out their duties and functions as organizers of government tasks in the health sector should have sufficient resources both in terms of quality and quantity to support promotive, curative, and rehabilitation activities through the application of soft skills. This type of research is observational, the approach used is cross sectional. The population in this study included all recipients of the Aceh Mental Hospital in March 2022, the selected sample was 100 people. Statistical analysis used is Partial Least Square with smartPLS 3.0. There is a significant influence on soft skills with service satisfaction at the Mental Hospital, thus soft skills can be a driving factor for service satisfaction officers at the Aceh Hospital ( 0.00 0 0.05) . There is the influence of physical evidence, reliability, responsiveness, empathy and assurance affect service satisfaction (42,986 > 1,984). The actor that most influences soft skills at the Aceh Mental Hospital is teamwork (37.247 > 1,984). The F actor that most influences service satisfaction is assurance. Based on the results of the study, it can be concluded that the soft skills of officers affect service satisfaction at the Aceh Provincial Hospital.